1994
DOI: 10.1088/0022-3727/27/6/034
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between active species density and iron nitride layer growth in Ar-N2-H2microwave post-discharges

Abstract: Correlations are demonstrated between the production of N, H and NH active species in an Ar-N2-H2 microwave flowing post-discharge and the thickness of epsilon and gamma ' layers on a pure iron substrate. The Fe2-3N, epsilon -layer thickness increases with N atom density when oxide layers are simultaneously removed by H atoms. A maximum has been found in the post-discharge reactivity when the H2/N2 density ratio is in the 10-3-10-2 range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Many possibilities for the use of TWSDs for surface processing and film deposition [12,149,[194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213], gas detoxification [214][215][216][217], for sterilization [218], for light sources [219][220][221][222][223] and lasers [224][225][226], for panel displays [227], for particle sources [228][229][230][231][232][233][234][235][236][237][238][239], for elementary analysis through atomic spectroscopy …”
Section: Travelling Wave-sustained Discharges: Brief History and Topimentioning
confidence: 99%
“…Many possibilities for the use of TWSDs for surface processing and film deposition [12,149,[194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213], gas detoxification [214][215][216][217], for sterilization [218], for light sources [219][220][221][222][223] and lasers [224][225][226], for panel displays [227], for particle sources [228][229][230][231][232][233][234][235][236][237][238][239], for elementary analysis through atomic spectroscopy …”
Section: Travelling Wave-sustained Discharges: Brief History and Topimentioning
confidence: 99%
“…Discharges and post‐discharges in N 2 –O 2 reactive gas mixtures with N 2 as the main gas component have been studied for polymer activation1 and bacteria inactivation 2. It has been also previously shown that adding H 2 to N 2 was efficient to eliminate the native oxide layer in the iron nitriding process 3…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen atom source is based on a microwave surface-wave discharge described elsewhere. 16,17 Briefly, a wave launcher ͑Surfatron 18 ͒ generates an electromagnetic surface-wave ͑at 520 MHz͒ which a͒ Author to whom correspondence should be sent. Electronic mail: tabbal@inrs-ener.uquebec.ca FIG.…”
mentioning
confidence: 99%
“…This postdischarge consists mainly of atomic and molecular nitrogen. 16,17 In these experiments, 50 sccm of an Ar/N 2 ͑1/1͒ mixture is flown through the discharge tube yielding a 2 mTorr pressure in the deposition chamber. The microwave power used is 70 W ͑82 W/cm 3 ͒.…”
mentioning
confidence: 99%